2009
DOI: 10.1111/j.1540-4560.2009.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Of Practicalities and Perspective: What Is Fair in Group Decision Making?

Abstract: Establishing fair procedures to regulate intragroup disagreements should engender cooperation while inhibiting conflict. Yet what is a "fair" procedure might vary for members of different factions. To understand perceptions of fairness in group decision making, the present research developed and utilized the Fair Group Procedures Scale (FGPS). Exploratory and confirmatory factor analyses revealed a four-factor structure along two dimensions: the means of distributing decision-making power (proportionality to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Sidanius and Pratto (1999) argue that all human societies are hierarchically organized; not only are individuals organized hierarchically by status (see Shelly & Shelly, 2009), but also subgroups within a group are differentiated by status (see Levin et al, 2009). Consequently, these subgroups develop different perspectives on group processes, with different views on what represents basic principles such as fairness (see Jacobs et al, 2009). Thus, as Chizhik et al (2009) suggested in the initial article in this volume, intragroup processes and intergroup relations are intimately intertwined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sidanius and Pratto (1999) argue that all human societies are hierarchically organized; not only are individuals organized hierarchically by status (see Shelly & Shelly, 2009), but also subgroups within a group are differentiated by status (see Levin et al, 2009). Consequently, these subgroups develop different perspectives on group processes, with different views on what represents basic principles such as fairness (see Jacobs et al, 2009). Thus, as Chizhik et al (2009) suggested in the initial article in this volume, intragroup processes and intergroup relations are intimately intertwined.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the same motivations for power and resources that underlie advantaged group members' motivation to maintain the status quo also form the basis of a disadvantaged group members' desire for social change (see also Jacobs, Christensen, & Prislin, this volume) . Blumer (1958) posited that people have a basic motivation to maintain or gain a relatively advantaged position for their group.…”
Section: Advantaged and Disadvantaged Group Members'perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…While the decision‐making processes within groups is important to investigate, it is also important to investigate group members’ perceptions of the decision‐making process. To this end, Jacobs, Christensen, and Prislin (2009) have examined how minority and majority factions within groups perceive the fairness of the decision‐making process. By presenting findings that point to the contextual nature of perceptions as to what is fair, the authors indicate that such perceptions can work to organize intragroup interactions through an affective filter that can modulate the perceived level of conflict and cooperation.…”
Section: Organization Of the Issuementioning
confidence: 99%